(x+8)(x-7)=16

Simple and best practice solution for (x+8)(x-7)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(x-7)=16 equation:


Simplifying
(x + 8)(x + -7) = 16

Reorder the terms:
(8 + x)(x + -7) = 16

Reorder the terms:
(8 + x)(-7 + x) = 16

Multiply (8 + x) * (-7 + x)
(8(-7 + x) + x(-7 + x)) = 16
((-7 * 8 + x * 8) + x(-7 + x)) = 16
((-56 + 8x) + x(-7 + x)) = 16
(-56 + 8x + (-7 * x + x * x)) = 16
(-56 + 8x + (-7x + x2)) = 16

Combine like terms: 8x + -7x = 1x
(-56 + 1x + x2) = 16

Solving
-56 + 1x + x2 = 16

Solving for variable 'x'.

Reorder the terms:
-56 + -16 + 1x + x2 = 16 + -16

Combine like terms: -56 + -16 = -72
-72 + 1x + x2 = 16 + -16

Combine like terms: 16 + -16 = 0
-72 + 1x + x2 = 0

Factor a trinomial.
(-9 + -1x)(8 + -1x) = 0

Subproblem 1

Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9

Subproblem 2

Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8

Solution

x = {-9, 8}

See similar equations:

| 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 | | (24)5= | | =7x+4(x+5) | | 4(x-6)+4=6x-8 | | 2r^2+18r+33=0 | | 2x+8=63 |

Equations solver categories